2019
DOI: 10.3390/ani9070461
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Graded Levels of Metabolizable Energy on Growth Performance and Carcass Characteristics of Slow-Growing Yellow-Feathered Male Chickens

Abstract: A dose-response study was conducted to investigate the metabolizable energy (ME) requirement for Lingnan chickens from 9 to 15 weeks of age. One thousand two hundred 8-week-old slow-growing yellow-feathered male chickens were allotted to five dietary ME levels (2805, 2897, 2997, 3095 and 3236 kcal/kg). The results revealed that the daily metabolizable energy intake increased (p < 0.01), whereas the feed intake and feed:gain ratio decreased linearly (p < 0.01) with the increment in dietary ME level. The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 39 publications
4
17
0
Order By: Relevance
“…Similar results were reported by Kalinowski et al [24] and Dozier et al [32]. Additionally, several studies indicated that evaluating the response of more than one variable to a dietary nutrient makes it difficult to determine a unique value of the nutrient requirement, i.e., the optimal level of any nutrient required for obtaining the best result of growth rate, body weight, feed intake, feed conversion ratio, meat quality, or immunity indices can differ [2,3,33]; this can explain the different values of optimal Met level for the different growth variables here.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Similar results were reported by Kalinowski et al [24] and Dozier et al [32]. Additionally, several studies indicated that evaluating the response of more than one variable to a dietary nutrient makes it difficult to determine a unique value of the nutrient requirement, i.e., the optimal level of any nutrient required for obtaining the best result of growth rate, body weight, feed intake, feed conversion ratio, meat quality, or immunity indices can differ [2,3,33]; this can explain the different values of optimal Met level for the different growth variables here.…”
Section: Discussionsupporting
confidence: 72%
“…The indigenous chickens have a recent increase in their commercial importance due to their favorable meat color and flavor, which highlights the need for comprehensive studies to enhance their feeding standards. However, only few researches on their nutrient requirements were conducted up till now [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, Wang et al (2014) reported a significant decrease in abdominal fat due to the decreasing dietary energy density of broiler chickens. In contrast, other researchers did not observe significant differences in carcase and breast yield, heart or liver due to the use of different dietary energy levels (Infante-Rodr ıguez et al 2016;Abouelezz et al 2019). This variation in response could be attributed to differences in the dietary energy level or broiler breed used.…”
Section: Discussionmentioning
confidence: 75%
“…Therefore, any strategy to reduce energy-related costs without adverse effect on broilers performance and their health may considerably increase the revenue of broiler production. So far, several studies have evaluated the effect of dietary energy on broiler growth performance (Infante-Rodriguez et al, 2016;Abouelezz et al, 2019). It is known that, aside from representing a potential energy source, the presence of dietary NSP may lead to higher intestinal viscosity, lower nutrient digestibility, impaired feed conversion ratio and consequently reduced bird growth performance (Lázaro et al, 2003;Meng et al, 2005).…”
Section: Introductionmentioning
confidence: 99%